জীবনানন্দ দাস দিনলিপি : লিটারারি নোটস ৩ (জুলাই ১৯২৫/এপ্রিল ১৯২৯-মার্চ ১৯৩০) - গুহ, ভূমেন্দ্র; মিএ, গৌতম (কলকাতা : প্রতিক্ষণ, 2009)
critical articles on literary notes of Jibanananda Das, 1899-1954, 20th century Bengali poet; includes text of notes and biographical information.
Donated by Akbar Ali Khan
In Bengali; includes English.
Keywords: Das, Jibanananda, -- 1899-1954, -- Criticism and interpretation; Das, Jibanananda, -- 1899-1954, -- Diaries; Poets, Bengali -- 20th century -- Biography; Bengali literature